The Yale Food Addiction Scale 2.0 and the modified Yale Food Addiction Scale 2.0 in Taiwan: Factor structure and concurrent validity - Chen, I-Hua; Huang, Po-Ching; Lin, Yi-Ching; Gan, Wan Ying; Fan, Chia-Wei; Yang, Wen-Chi; Tung, Serene En Hui; Poon, Wai Chuen; Griffiths, Mark D.; Lin, Chung-Ying (Frontiers in Psychiatry, 2022)
The most widely used instruments to assess food addiction – the Yale Food Addiction Scale 2.0 (YFAS 2.0) and its modified version (mYFAS 2.0) – have not been validated in a Taiwanese population. The present study compared the psychometric properties between the Taiwan versions of YFAS 2.0 and mYFAS 2.0 among university students. An online survey comprising the YFAS 2.0, mYFAS 2.0, Weight Self-Stigma Questionnaire (WSSQ) and International Physical Activity Questionnaire–Short Form (IPAQ-SF) were used to assess food addiction, self-stigma, and physical activity. All participants (n=687; mean age=24.00 years [SD±4.48 years]; 407 females [59.2%]) completed the entire survey at baseline and then completed the YFAS 2.0 and mYFAS 2.0 again three months later. The results of confirmatory factor analysis (CFA) indicated that the YFAS 2.0 and mYFAS 2.0 both shared a similar single-factor solution. In addition, both the YFAS 2.0 and mYFAS 2.0 reported good internal consistency (Cronbach’s alpha=0.90 and 0.89), good test-retest reliability (ICC=0.71 and 0.69), and good concurrent validity with the total scores being strongly associated with the WSSQ (r=0.54 and 0.57; p<0.01), and less strongly associated with BMI (r=0.17 and 0.13; p<0.01) and IPAQ-SF (r=0.23 and 0.25; p<0.01). Based on the findings, the Taiwan versions of the YFAS 2.0 and mYFAS 2.0 appear to be valid and reliable instruments assessing food addiction.